Effectiveness of Brown Algae Extract to Reduce Serum Malondialdehyde and Protein Carbonyl Levels in Streptozotocin-Induced Sprague Dawley Rats - Batubara, Lusiana; Kristina, Tri N.; Rachmawati, Banundari (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2016)
Introduction: Brown algae (Sargassum duplicatum) contains bioactive compound with natural antioxidant that may potentially decrease lipid peroxidation and protein oxidation process in diabetes mellitus. Objective: to prove the effectiveness of brown algae extract administration (150mg/kgBW; 300mg/kgBW and 450 mg/kGBW respectively) in reducing serum MDA and PCO levels in streptozotocin-induced sprague dawley rat. Methods: This experiment study used the post test only control group design. Twenty eight (28) Sprague dawley rats induced with Streptozotocin (STZ) 40 mg/kgBW (i.p) were divided into four groups (n=7). The first group was diabetic non treated group (control). The second to fourth groups were the diabetic rats which given brown algae extract (150mg/kgBW; 300mg/kgBW and 450 mg/kgBW respectively) for 30 days. Serum MDA and PCO levels were examined by using ELISA method. Data were analyzed using one way ANOVA.Results: There were no significant differences in serum MDA levels among groups (p=0,405). However, serum PCO level in group administered with 450mg/kgBW of brown algae extract decreased significantly compared to control group (p=0.001), group administered with 150mg/kgBW (p=0.001) and 300mg/kgBW (p=0,037). Conclusion: Administration of brown algae extract did not decrease serum MDA levels significantly. Administration of 450mg/kgBW brown algae extract is effective to decrease serum PCO level significantly.